Endogamia y exogamia en la sociedad colonial cartaginesa 1738-1821 - Acuña León, María de los Angeles (1991)
A study on marriage patterns in the city of Cartago, Costa Rica, from 1738 to 1821. The discussion of endodagamous and exogamus marriages helps explain the process of racial mixture and the differential growth of ethnic groups inhabiting of colonial capital.